An Analysis Of Translation Strategies On Idioms Found In Novel Babel; Or The Necessity Of Violence: An Arcane History Of The Oxford Translators’ Revolution - Monica, Stephany; Kurais, Ardillah (International Journal of English Language and Pedagogy, 2025)
This study aimed to analyze and identify the strategies used in idiom translating and the most dominant strategy utilized in “Babel; or The Necessity of Violence: An Arcane History of the Oxford Translators’ Revolution” novel by R. F. Kuang from English to Indonesian. The data were collected by listing the idioms in the source text and their corresponding translation in the target text, which is entitled, Babel; atau Pertumpahan Darah: Sejarah Gelap Revolusi Penerjemah Oxford translated by Siska Nurohmah; identifying the idioms by classifying the idioms found using Fernando’s theory about the classification of idiom types. The method used in this research was descriptive qualitative, where the collected data was later analyzed according to Baker’s idiom translation. Based on the results of data analysis that had been obtained with idiom translation strategy used by translators in chapters one and two is 11 translations using similar meaning and form strategy, 2 translations using similar meaning and dissimilar form, 20 translations by paraphrasing, and 1 translation by omission or ellipsis. Paraphrasing was the most used strategy in this translation, with a percentage of 58.82%